Plants with antinociceptive activity from MSS 3048 for shingles treatment: a molecular docking study of the active compounds with P2X4 receptor - Zulkifli, Farah Nazihah; Ahmad Nadzirin, Izzuddin (IIUM Press, 2024)
Malay medical manuscripts (MMM) discuss diseases and remedies according to Malay traditional medicine. One of them, MSS 3048, compiles a variety of diseases including shingles; a viral disease that manifests itself with neuropathic pain. One of the mechanisms that cause neuropathic pain is through the activation of P2X4, an ionotropic receptor. Hence, one of the strategies for treating neuropathic pain is by inhibiting the receptor. However, current antinociceptive drug can cause serious side effects like respiratory depression. Thus, the goal is to identify potential compounds that can block P2X4 based on the information from MSS 3048 and in silico study. Firstly, the content of MSS 3048 was analysed to find the plants used for shingles. Then, the active compounds possessed by the plants were studied and the ones that had been shown to have antinociceptive effect based on literature studies were selected. Then the 3D structures of the plant's active ingredients were docked on the human P2X4 homology model using Autodock Vina software. The software produced results that showed the binding affinity of the active ingredients towards P2X4. The inhibitors’ affinity was compared to known ligands which are 5- (3-Bromophenyl)-1,3-dihydro-2H-benzofuro[3,2-e]-1,4-diazepin-2-one(5-BDBD), adenosine triphosphate (ATP), cytidine triphosphate (CTP) and α,β-methylene ATP (α,β-meATP) as a reference. The result shows that the top six compounds with high affinity towards P2X4 are dioscin, ampelopsin F, corilagin, ellagic acid pentoside, punicalin and proanthocyanidins. Then the top six compounds were analysed by looking at the chemical interaction. The compound that showed the highest potential was dioscin, one of the compounds from nipah palm, with binding affinity of -9.87 kcal/mol. This compound may have the potential to block P2X4 receptor and could be studied in in vitro and in vivo study before being used as treatment for shingles.